The role of ED in Portuguese SMEs’ Internationalization : the case of the Internationalization of Portuguese SMEs to the USA/California - Ferreira, Filipa de Almeida Fernandes (2022)
In the last decades, the focus on Economic Diplomacy (ED) has intensified, as governments from most countries have been realizing that, in a globalized world, there is the urge to internationalize. In this sense, to boost a country’s growth, ED must impact the companies. This dissertation attempts to assess the role of ED in the internationalization process of Portuguese firms, with a focus on the US and, particularly, California. For that, the method followed was based on the case study research strategy, under a qualitative approach, complemented by some quantitative data. Besides, some interviews were conducted in order to obtain targeted data on the subject. My internship in AICEP’s San Francisco delegation fostered my interest in the topic and was instrumental in the data collection for this study. The main findings of this thesis lead to the conclusion that ED, by fostering exports, plays a crucial role in the internationalization process, holding an extremely positive impact on firms and, consequently, on the country. For future research, the measurement of the effect of ED in a country should be improved because, although it is demonstrated that, in general, its impact is positive, there are not many data that allow to disentangle the effective impact of ED per se.